KEMAMPUAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL MEMODERASI HUBUNGAN KINERJA KEUANGAN DENGAN NILAI PERUSAHAAN - Amelia Permana, Desak Made Riza (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
ABSTRACT This study aims to determine the capability of corporate social responsibility disclosure to moderate the relationship between financial performance with value firm. The population in this study is listed firms in Indeks Kompas 100 during the period 2008-2011. The technique used to determine samples was using purposive sampling therefore the total number of sample are 38 firms with 144 observations. Independent variable in this study is financial performance, dependent variable is value firm, and corporate social responsibility disclosure as moderating variable. Hypothesis testing studies used residual test. The residual test results showed that the corporate social responsibility disclosure has no capability to moderate the relationship between financial performance with value firm. Keywords: ROE, Tobin’s Q, Corporate Social Responsibility Disclosures